2000
DOI: 10.1007/s11745-000-0636-5
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of an 11(R)‐ and 12(S)‐lipoxygenase activity in ovaries of the mussel Mytilus edulis

Abstract: Eicosanoid biosynthesis was investigated in mussel gonads by incubation of tissue homogenates with radiolabeled arachidonic acid and analysis of the products by radio-high-performance liquid chromatography. No radiolabeled metabolites were formed in homogenates of testes, but two major metabolites were synthesized by ovarian preparations. The radiolabeled metabolites were analyzed by mass spectrometry and chiral chromatography and identified as 11 (R)-hydroxy-5,8,1 2,14-eicosatetraenoic acid and 12(S)-hydroxy-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…The present differences in fatty acid compositions in the testis and ovary of limpets according to sex may be to a clue for understanding not only the reproductive cycle in marine invertebrates but also mechanisms of biologically active lipid metabolites known as eicosanoids that are essential to reproductive physiology (12)(13)(14).…”
Section: Resultsmentioning
confidence: 99%
“…The present differences in fatty acid compositions in the testis and ovary of limpets according to sex may be to a clue for understanding not only the reproductive cycle in marine invertebrates but also mechanisms of biologically active lipid metabolites known as eicosanoids that are essential to reproductive physiology (12)(13)(14).…”
Section: Resultsmentioning
confidence: 99%
“…Invertebrates include multiple groups of living organisms such as insect, crap, lobster, snail, clam, octopus, starfish, sea urchin, worm and sponge. Functional LOX isoforms from various invertebrates have been characterized as fusion or nonfusion proteins in different corals [135][136][137][138][139][140], in starfish oocytes [141], in the eggs of a sea urchin [142] and in the ovaries and oocytes of different mussels (Mylitis edulis, Spisula solidissima) [143,144]. Recently the distribution of LOX isoforms in 14 different invertebrate species was explored [145] and the authors found putative LOX-like sequences in 10 of them (Ciona intestinalis, Saccoglossus kowalevski, Strongylocentrotus purpuratus, Crassostrea gigas, Lottia gigantea, Capitella teleta, Helobdella robusta, Acropora digitifera, Nematostella vectensis, Trichoplax adhaerens).…”
Section: Lox In Invertebratesmentioning
confidence: 99%
“…The 2,4-decadienals of marine algal volatile compounds have been suggested to be produced via 11-hydroperoxyicosatetraenoic acid (HPITE) from arachidonic acid in marine green algal 11-LOX pathway [9]. The 11-HPITE has also been named in our studies as well as in other literatures [6,10].…”
Section: Introductionmentioning
confidence: 76%